2015
DOI: 10.1021/acs.energyfuels.5b01807
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Mediated Separation of Carbon Dioxide from Flue Gas

Abstract: The proton-coupled electron transfer (PCET) reaction of a quinone has been used to create a pH gradient capable of the active pumping of CO2 through a liquid membrane. The quinone redox couples, hydroquinone/benzoquinone and 2,6-dimethylbenzoquinone/2,6-dimethylhydroquinone, have been investigated in the proton transfer mechanisms associated with electron transfer in sodium bicarbonate solutions. These same conditions have then been applied to an active liquid membrane for proton pumping across a membrane elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…By considering the electrolysis data in Figures and together with the stoichiometry of Equations (1)–(4), we can infer that the carbonation rate at the cathode increases with current density. Indeed, electrochemically mediated CO 2 ‐separation schemes leveraging this phenomenon have been proposed . Accordingly, we hypothesize that GDE failure is initiated by carbonate salt precipitation followed by rapid electrolyte percolation through the crystallites, which retards CO 2 transport sufficiently as to necessitate H 2 generation through water splitting to meet imposed galvanostatic requirements.…”
Section: Resultsmentioning
confidence: 94%
“…By considering the electrolysis data in Figures and together with the stoichiometry of Equations (1)–(4), we can infer that the carbonation rate at the cathode increases with current density. Indeed, electrochemically mediated CO 2 ‐separation schemes leveraging this phenomenon have been proposed . Accordingly, we hypothesize that GDE failure is initiated by carbonate salt precipitation followed by rapid electrolyte percolation through the crystallites, which retards CO 2 transport sufficiently as to necessitate H 2 generation through water splitting to meet imposed galvanostatic requirements.…”
Section: Resultsmentioning
confidence: 94%
“…Indeed, electrochemically-mediated CO2 separation schema leveraging this phenomenon have been proposed. [56][57][58] Accordingly, we hypothesize that GDE failure is initiated by carbonate salt precipitation followed by rapid electrolyte percolation through the crystallites which retards CO2 transport sufficiently as to necessitate H2 generation via water splitting to meet imposed galvanostatic requirements. A similar electrode degradation mechanism has previously been proposed for air-fed, flowing electrolyte alkaline fuel cells.…”
Section: Co2 Electrolysis and Capacitance Measurementsmentioning
confidence: 99%
“…2b Calculated assuming cell operates in steady-state (hydrogen oxidation reaction at pH 0, water reduction at pH14), and that 100% of H 2 gas generated at the cathode is recovered and fed into the anode.The use of redox-active species and cell architectures that impose minimal kinetic losses while preserving the pH gradient would be crucial to realizing electrochemical CCS at low energetic cost. Watkins et al[51] have demonstrated CO2 separation from flue gas using a pH gradient In addition to minimal energetic losses, another important criterion for wide scale adoption of CO2 separation technology is the use of low-cost cell components and working fluids. The process described here can, in principle, use water-soluble molecules and aqueous electrolytes.…”
mentioning
confidence: 99%
“…An inlet composition with 16% CO 2 was reported, but no exit pressure was given. The experimental electrical work input was calculated for a potential of 1.0 V applied across the cell, with CO 2 captured in the form of HCO 3and released back to CO 2 (g) with 16% mass transport efficiency (seeTable 1in ref [51]…”
mentioning
confidence: 99%